2 - La Cour Suprême, la compétition électorale et la continuité politique au Cameroun: La construction de la démocratisation passive: by Luc Sindjoun - Luc Sindjoun, (Africa Development, 1994)
In Africa, a tremendous confusion currently exists between the concepts of liberalization and political democratizations as a result the organization of numerous national conferences. In Cameroon, Paul Biya's re-election as President on 11th October 1992 is a proof of the failure of the Supreme Court in its mission to arbitrate in electoral disputes and maintain independence in dealing with the results of the election. The author argues that what has happened can be called conservative liberalization and passive democratization because the Executive has succeeded in keeping its narrow advantages with help of a controlled magistrature in spite of the growing opposition.